Military Geography - Sali, Dr. M. L. (New Dilhi Manas Publications, 2009)
The book is about Balochistan, which comprises almost half the territory of Pakistan and has been in turmoil on and off for the past six decades. The current bout of violence in traditional Baloch lands, which form the part of Pakistan, Iran and Afghanistan, is the strongest assertion of Baloch identity. The challenge is the strongest in Pakistani Balochistan, where Pakistan is undertaking large scale developmental project to provide fillip to Pakistani economy but the Baloch nationalists have been viewing these developmental projects with suspicion and consider them to be the instruments for the colonisation of traditional Baloch land. Pakistani state has tended to dismiss the turbulence in Balochistan as usual tribal mischief. However, the nationalist support transcends tribal barriers and the Baloch have genuine grievances against the State. The book covers the recent manifestation of violence in Balochistan in historical context, current revival of violence, its causes, modus operandi and implications.
Include Map, Tables and Index
Keywords: Military geography -- India